Gender differences in motivation toward learning EFL skills among international students - Hariharan a/l N. Krishnasamy, Hashim Ahmed Samir, (Opción, 2019)
This paper aims to examine the effects of the gender differences on learners‟ motivation in learning the four skills of English as a foreign language as well as to identify the proper types of motivation for males and females via a qualitative semi-structured interview. The findings showed that all the males have extrinsic motivation in all four skills. On the other hand, females differ among themselves in their motivation. In conclusion, it is also the teachers‟ responsibility to guide and direct their learners to achieve better outcomes in learning the four EFL skills.